Ectoparasites of domesticated animals in a rural Barangay, Davao City, Mindanao Island, Philippines - Delima-Baron, Elsa May; S. Ruales, Cyrell Ann (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
As the reemergence of maladies in humans caused by bacterial species continues, the need to identify and determine possible routes of infection of bacterial pathogens is necessary. Special focus on the contribution of ectoparasites that infest domesticated animals appears timely especially in suburban or rural settings where domesticated animals form part of their communities. It is for this purpose that infested domesticated animals and their associated ectoparasites of a rural community in Davao City, Mindanao, Philippines were accounted. Ectoparasites were sourced from domesticated animals with hair, feather, and fur and were extracted manually from the hosts and identified based on morphological features. Fifty host domesticated animals were inspected, 41 of which were infested with ectoparasites. A total of 433 individuals of ectoparasites were found: 87 (in chicken), 199 (in dogs), 94 (in cat), nine (in dove), and 44 (in goat) representing 10 species. Except for goats, 41% of the domesticated animals were infested with more than one species of ectoparasite. Ten species of ectoparasites were identified with lice species dominating the pool of ectoparasites identified: Lice- 8; flea - 1; tick -1. All host domesticated animals were infested with at least one louse species while ticks were found only in dogs, and the flea species extracted only from dogs and cats. Data suggest the differential distribution of ectoparasites among domesticated animals in this rural barangay. Moreover, ectoparasites may transfer from one domesticated animal to another given the occurrence of several ectoparasite species in more than one inspected domesticated animal.